Rural energy poverty: An investigation into socioeconomic drivers and implications for off-grid households in the Eastern Cape Province, South Africa - Mahali Elizabeth Lesala; Patrick Mukumba; Obileke KeChrist (Economies, 2025)
Energy poverty is a significant barrier to sustainable development, limiting access to modern energy solutions and exacerbating socioeconomic inequalities in South Africa. This research identifies key socioeconomic factors contributing to energy poverty among off-grid households using the household-specific energy poverty line. A cross-sectional study was conducted using a well-structured questionnaire among 53 households. The findings reveal significant gender disparities, with female-headed households being more vulnerable to energy poverty, which continues to subject them to economic hardship and social marginalization. Additionally, while larger households generally face higher energy demands, they were found to be less likely to experience energy poverty. The findings also challenge the 'energy ladder hypothesis' by showing that education, while potentially enabling better energy awareness, does not guarantee improved energy access in off-grid areas due to infrastructural limitations. Social grant dependency was found to be strongly correlated with energy poverty, underscoring the inadequacy of income transfers in addressing the systemic barriers to energy access. The findings emphasize the need for multidimensional, gender-responsive policy interventions that address both infrastructural and socioeconomic barriers to energy access, particularly in rural South Africa. These insights are crucial for developing targeted interventions to alleviate energy poverty and foster sustainable development in off-grid communities.
Keywords: 330; energy access; energy poverty; off-grid households; socioeconomic drivers